The Role of Banking Companies in Controlling Money Laundering Operations Applied Study on Banking Companies in Basra Governorate (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The aim of this research is to clarify the role of the banking companies in monitoring the operations of the money laundering in the province of Basra through the knowledge of the methods that are followed by these companies. In this study, the researcher has used a questionnaire that was prepared based on the previous studies and by the additions that were done by the arbitrators and the researcher in order to measure the variables of the study. The researcher has distributed (90) questionnaires to the employees in the banking companies. Moreover, the researcher has used SPSS program for the statistical analysis based on the five-dimensional Liker scale, the mean, the standard deviation, and the relative weight.The search a number of results. The most important one is that the role that is played by the banking companies has a strong impact on controlling the operations of the money laundering. In addition, the researcher has also a number of recommendations. The most important ones are; banking companies should pay an extra attention in applying the methods of their followed oversights and increasing the cooperation and the coordination with the Central Bank by appointing a specified employee to follow up the procedures of money laundering operations that are issued